2009
DOI: 10.1186/1477-5956-7-21
|View full text |Cite
|
Sign up to set email alerts
|

Proteins recruited by SH3 domains of Ruk/CIN85 adaptor identified by LC-MS/MS

Abstract: Background: Ruk/CIN85 is a mammalian adaptor molecule with three SH3 domains. Using its SH3 domains Ruk/CIN85 can cluster multiple proteins and protein complexes, and, consequently, facilitates organisation of elaborate protein interaction networks with diverse regulatory roles. Previous research linked Ruk/CIN85 with the regulation of vesicle-mediated transport and cancer cell invasiveness. Despite the recent findings, precise molecular functions of Ruk/CIN85 in these processes remain largely elusive and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 92 publications
5
46
1
1
Order By: Relevance
“…This emphasizes the importance of CBL-associated deregulation of signaling in chronic myeloid diseases and constitutes an incentive to look for alterations in other members of the CBL/CIN85 pathway. 12 In that respect we found a gain of the gene encoding MAP3K4, an interactor of CIN85, 13 in a RAEB1 with complex aCGH profile, and a gain of the gene encoding the CBL interactor ARHGEF7/bPIX in an RCMD in a reported study. 14 Whether other E3 ubiquitin ligases (for example, AHR or SCF components) may have a role in these diseases also needs to be investigated.…”
mentioning
confidence: 54%
“…This emphasizes the importance of CBL-associated deregulation of signaling in chronic myeloid diseases and constitutes an incentive to look for alterations in other members of the CBL/CIN85 pathway. 12 In that respect we found a gain of the gene encoding MAP3K4, an interactor of CIN85, 13 in a RAEB1 with complex aCGH profile, and a gain of the gene encoding the CBL interactor ARHGEF7/bPIX in an RCMD in a reported study. 14 Whether other E3 ubiquitin ligases (for example, AHR or SCF components) may have a role in these diseases also needs to be investigated.…”
mentioning
confidence: 54%
“…on May 11, 2018. by guest www.bloodjournal.org From function of coated vesicles. 25 Similarly, early studies showed a characteristic feature of CIN85 in the formation of clathrin-coated vesicles during the internalization of RTKs such as EGFRs in nonimmune cells. 18,19 Brain-specific CIN85-deficient mice manifest impaired internalization of D2 dopamine receptors, which belong to the 7-transmembrane G protein-coupled receptor superfamily.…”
Section: Discussionmentioning
confidence: 93%
“…1,2 Because SH3 domains play an important role in the function of CIN85, 25 we focused on For personal use only. on May 11, 2018. by guest www.bloodjournal.org From tyrosine-phosphorylated molecules downstream of the BCR that could associate with the SH3 domains of CIN85.…”
Section: Cin85 Associates With Cbl and Blnk And Regulates Their Phospmentioning
confidence: 99%
See 1 more Smart Citation
“…Insights & Perspectives ..... PDGFR [28] p130Cas [70] Vinexin [76] PR130 [47] FcgRIIB [64] p85a [62] Filamin [77] SHIP1 [82] FcgRIIA [65] APS [71] Actin [77] M-CSFR [66] DOK-1 [72] Intersectin1 [78] cMET [67] JIP-1 [73] ARAP-3 [79] ABL [62] CD2AP [74] CIN-85 [80] EphrinA2R [68] SH3YL1 [54] Lamin A/C [22] JIP-1, JNK-interacting protein 1; PTP1B, protein-tyrosine phosphatase 1B; CD2AP, CD2-associated protein; SH3YL1, SH3 domain-containing Ysc84-like 1; PDGFR, platelet-derived growth factor receptor; EGFR, epidermal growth factor receptor; M-CSFR, macrophage colony-stimulating factor receptor; cMET, hepatocyte growth factor (HGF/SF) receptor; EphrinA2R, ephrinA2 receptor; ARAP-3, Arf GAP, Rho GAP, ankyrin repeat and PH domains. It is proposed that SHIP2 is phosphorylated to phospho SHIP2 (pSHIP2) S132 in the cytoplasm.…”
Section: W Elong Edimo Et Almentioning
confidence: 99%